Mercers' Chapel, As Rebuilt After The Fire. (From An Old Print.) (See Page 381) (Tufts Archival Research Center, 2005)
This illustration is from Walter Thornbury "Old and new London, a narrative of its history, its people, and its places, vol. 1"